Biomarker testing in lung cancer: from bench to bedside - Ullas Batra; Shrinidhi Nathany (Oncology Reviews)
Non-small-cell lung cancer (NSCLC) is the poster child of personalized medicine. With increased knowledge about biomarkers and the consequent improvement in survival rates, NSCLC has changed from being a therapeutic nihilistic disease to that characterized by therapeutic enthusiasm. The routine biomarkers tested in NSCLC are EGFR, ALK, and ROS1. However, several additional biomarkers have been added to the diagnostic landscape. Current guidelines recommend testing at least seven biomarkers upfront at the time of NSCLC diagnosis—emphasizing the wide range of targets and corresponding therapies that can be leveraged for disease management. Sequential single-gene testing is not only time-consuming but also leads to tissue exhaustion. Multigene panel testing using next-generation sequencing (NGS) offers an attractive diagnostic substitute that aligns with the evolving dynamics of precision medicine. NGS enables the identification of point mutations, insertions, deletions, copy number alterations, fusion genes, and microsatellite instability information needed to guide the potential use of targeted therapy. This article reviews the existing guidelines, proposed recommendations for NGS in non-squamous NSCLC, real-world data on its use, and the advantages of adopting broader panel-based NGS testing over single-gene testing.